2016
DOI: 10.1039/c6ra16984h
|View full text |Cite
|
Sign up to set email alerts
|

Structures, formation mechanisms, and ion-exchange properties of α-, β-, and γ-Na2TiO3

Abstract: The structure of β-Na2TiO3 was refined. The formation/transformation mechanisms and ion-exchange properties of α-, β-, and γ-Na2TiO3 were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…5) were in agreement with the XRD results. At 900°C, the peaks of rutile TiO 2 can be e fibers annealed at 900°C in air seen on the spectra (the peaks at around 243 cm -1 , 447 cm -1 , and 612 cm -1 can be, respectively, assigned to the second-order Raman scattering, E g and A 1g modes of rutile TiO 2 [28,30]), and also some small peaks of the anatase remained. However, at 550°C, only the anatase TiO 2 peaks were visible.…”
Section: Resultsmentioning
confidence: 97%
“…5) were in agreement with the XRD results. At 900°C, the peaks of rutile TiO 2 can be e fibers annealed at 900°C in air seen on the spectra (the peaks at around 243 cm -1 , 447 cm -1 , and 612 cm -1 can be, respectively, assigned to the second-order Raman scattering, E g and A 1g modes of rutile TiO 2 [28,30]), and also some small peaks of the anatase remained. However, at 550°C, only the anatase TiO 2 peaks were visible.…”
Section: Resultsmentioning
confidence: 97%
“…1) We found that NaOH could react with TiO 2 to form titanate, which is in amorphous state and dispersed at the surface of the catalyst (Figure d and S10). Through comparing crystal structure parameters, the bond length of Ti–O in Na 2 TiO 3 (a common titanate as example) is much longer than that in TiO 2 , i.e., 2.02–2.40 Å in Na 2 TiO 3 and 1.937–1.983 Å in TiO 2 , respectively. , Besides, titanate material can be used as oxygen transport membrane for its excellent chemical and redox stability at high temperature . Therefore, the weaker Ti–O bond along with the mobility of O in titanate may result in easier reduction of the support.…”
mentioning
confidence: 99%
“…7,8 This suggests that the changes in the grain size are probably somehow related with presence of the Na-rich phase. Some sodium titanates have melting temperatures close to 1000 • C. 26 Another scenario is related to increased concentration of oxygen vacancies, according to assumptions described above.…”
Section: Resultsmentioning
confidence: 99%